If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 10 = 6x + -2 Reorder the terms: 10 + 5x = 6x + -2 Reorder the terms: 10 + 5x = -2 + 6x Solving 10 + 5x = -2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 10 + 5x + -6x = -2 + 6x + -6x Combine like terms: 5x + -6x = -1x 10 + -1x = -2 + 6x + -6x Combine like terms: 6x + -6x = 0 10 + -1x = -2 + 0 10 + -1x = -2 Add '-10' to each side of the equation. 10 + -10 + -1x = -2 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = -2 + -10 -1x = -2 + -10 Combine like terms: -2 + -10 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| 7(10+5x)=245 | | 7(4-3x)=-35 | | -3(1+4x)=69 | | -3(1+4x)=3 | | 7m^2-9m^2+10m^2= | | 3(1+7x)=3 | | -7(2+4x)=-154 | | -6(4x+6)=-156 | | 6d-2h+5h-d= | | 2x^2+6x=-2 | | -6(3x+4)=-240 | | 5p+5=10+4p | | x(x+5)(x-2)=0 | | 5(-2x-6)=-60 | | x+(x-6)+(x+5)=44 | | 4(2x-1)=-4 | | 2x-8=x-1-3 | | -7x-7=-37+3x | | 2x^2+20x-10=0 | | 3(t+36)=15 | | -3(-1x-8)=15 | | 3(-8+6x)=-42 | | 9=x+0.5x | | 2x+4y=38 | | 2x^2=18+51 | | 2l^2=18+1 | | -2(3-5x)=-126 | | 0=2x^4+x^3-26x^2-36x-12 | | -20=-10x^2-40x-10 | | 4-8x=-32 | | 3(5x+9)=-93 | | 3(5x+9)=-39 |